Geriatric Game 0.1: Teknologi Ramah Lingkungan untuk Meningkatkan Fungsi Kognitif Lansia di RS Radjiman Wediodiningrat - Hilda Mazarina Devi; Yanti Rosdiana; Amalia Kusumaningsih (Jurnal Akademika Baiturrahim Jambi, 2026)
The global population of older adults is increasing steadily worldwide. The United Nations projects that by 2050, one in six people globally will be aged 65 years or older, many of whom are at risk of cognitive decline. Addressing both health and environmental concerns, Geriatric Game 0.1 was developed as an eco-friendly cognitive stimulation tool for older adults, utilizing recycled plastic bottle caps. This innovation aims to reduce environmental pollution, generate economic value, and promote a harmonious relationship between humans and the environment. This study aimed to examine the effects of Geriatric Game 0.1 combined with recreational brain gym therapy on cognitive function among older adults. Cognitive function was assessed using the Mini-Mental State Examination (MMSE-11). A randomized controlled trial design was applied. The intervention group received two types of Geriatric Game 0.1 (puzzle and tic-tac-toe) alongside brain gym exercises, while the control group received brain gym therapy alone. Both groups participated in ten therapy sessions conducted over a three-month period (01 August– 30 October 2025). The study involved 15 older adults each group who admitted to the Psychogeriatric Ward of Dr. Radjiman Wediodiningrat Hospital, Lawang. Pre- and post-intervention data were analyzed using paired t-tests. The results demonstrated a statistically significant improvement in cognitive function in the intervention group (p<0.05). The mean MMSE score increased from 20 (moderate cognitive impairment) at baseline to 23.7 (mild cognitive impairment), reflecting a mean improvement of 3.7 points. Significant gains were observed in orientation, attention and calculation, and recall domains. In conclusion, integrating Geriatric Game 0.1 with brain gym therapy is an effective and sustainable nursing intervention for older adults with cognitive decline, while simultaneously supporting circular economy principles and strengthening nurse–older adult relationships